Short term outcome following acute phase switch among P2Y12 inhibitors in patients presenting with acute coronary syndrome treated with PCI: A systematic review and meta-analysis including 22, 500 patients from 14 studies. (March 2019) - Cerrato, Enrico; Bianco, Matteo; Bagai, Akshay; De Luca, Leonardo; Biscaglia, Simone; Luciano, Alessia; Destefanis, Paola; Quadri, Giorgio; Meynet, Ilaria; Gravinese, Carol; Chinaglia, Alessandra; Goodman, Shaun G.; et al.
Abstract: Introduction: The efficacy and safety of switching P2Y12 receptor antagonists in patients admitted for acute coronary syndrome (ACS) remain unclear. We assessed the short-term clinical outcomes (in-hospital and within 30 days) of switching P2Y12 inhibitor (P2Y12 I) drugs versus maintaining the same regimen by performing a comprehensive review and meta-analysis of available data. Methods: MEDLINE/PubMed/SCOPUS/Cochrane databases were screened for studies regarding switching of P2Y12 I in patients with ACS that reported 30 days follow-up. Major cardiac events (MACE) and bleeding were compared between patients who were switched/not switched. Results: 22, 500 patients from 14 studies were included. Unstable angina/non-ST elevation myocardial infarction (62.0%, interquartile range, 52.8%–68.0%) was the most common clinical presentation. The total number switched was 4294 (19.1%); escalation in 3416 (79.5%) patients (from clopidogrel to prasugrel, 62.9%) and de-escalation in 18.5%. Pooled analysis revealed no significant differences in MACE for any comparison; risk of bleeding was significantly increased among switched patients overall (odds ratio [OR], 1.60; 95% confidence interval [CI] 1.22–2.10) and increased in the escalation group (OR, 1.51; 95% CI, 1.06–2.16). Conclusions: Among patients presenting with ACS, switching from one P2Y12 I agent to another in the acute phase seems associated with a short-term increased risk of bleeding. Accurate upfront selection and prescription of a P2Y12 I based on ischemic and bleeding risks is paramount to avoid adverse events switching-related during hospitalization and in the first 30 days.